Traffic flow model for vehicular network - Nafi, Nazmus Shaker; Hasan, M.K.; Hassan Abdalla Hashim, Aisha (2012)
Intelligent Traffic Management (ITM) system promises to reduce the traffic congestion, intelligent intersection management as well as the smart dissemination of the informatics to control the traffic flow. Development of any Intelligent Transportation System (ITS) applications requires realistic road traffic model to analysis the performance. Service rate or service time is one of the most important components of any vehicular traffic model to analyze its properties. Traffic flow model which is based on any existing queuing methods have different properties to analyze such delay, queuing length, saturation flow (for fixed cycle of signaling period) etc. Depending on the on road traffic capacity and the intensity of the vehicle the service rate will determine and also the mentioned properties. In this paper, the model involves the analysis of the traffic parameters of an intersection with MM1 queuing system to optimize the service rate that is needed to develop the long term evaluation (LTE) based intersection management system (IMS).